Evaluasi Kapasitas Apron Utara Bandar Udara Internasional I Gusti Ngurah Rai Bali - Wicaksono, Denia Fertika; Surahman, Luky (Jurnal Teknik Transportasi, 2024)
The apron capacity of I Gusti Ngurah Rai International Airport is an important factor in handling the increasing number of aircraft movements. This research utilizes the FAA (Federal Aviation Administration) method to evaluate the apron capacity and determine the need for apron expansion. Operational data of the airport, including the number and types of aircraft operating on the apron, as well as other related activities, were collected and analyzed. Subsequently, using the FAA method, the Gate Hourly Base Capacity (G*) value was calculated based on the appropriate ratio (R) for the existing apron conditions. The evaluation results indicate that the current apron capacity is sufficient to accommodate the current number of aircraft movements. Based on the FAA calculations, the Gate Hourly Base Capacity (G*) value for the relevant ratio shows that the apron can handle the current number of operating aircraft without significant physical expansion. This research provides a better understanding of the apron capacity of I Gusti Ngurah Rai International Airport and contributes to the development of effective apron management strategies. By ensuring adequate apron capacity, the airport can meet the needs of aviation service users and promote the growth of the aviation industry in the region. Keywords : airport, apron, capacity, evaluation, FAA method, expansion.